Congenital ocular and adnexal disorders in reptiles. (1st May 2012) - Sabater, Mikel; Pérez, Marisa
Abstract Ocular and adnexal congenital disorders are those that manifest at birth and could involve single or multiple tissues. Several abnormalities have been reported in literature affecting reptilian ocular and/or adnexal tissues. The objectives of this review are: (i) review those disorders previously reported in reptile literature; (ii) present new cases; (iii) provide a basic classification of them according to the moment of occurrence and (iv) indirectly, encourage the clinician dealing with these cases to go further in their diagnosis. The authors consider that categorizing ocular and adnexal congenital disorders could help the clinician to deal with them. The categorization of these disorders required an intense review of cases previously reported in literature and allows the authors suspect that some of them could not have been accurately diagnosed according to the definitions of the anomalies and/or not accurately described. The authors consider that ocular and adnexal congenital disorders could have been underestimated in reptiles and further studies could be helpful to promote the description of new disorders and to expand the knowledge about those previously reported. The review will first describe abnormalities reported during organogenesis (describing possible etiopathogenesis, cases reported, an approach to their diagnosis and recommended therapeutic options).Then a mention of the ocular disorders occurring after organogenesis is made. These disorders are divided when possible in those affecting all or most part of the globe and those affecting only specific tissues (surface ectoderm, neurocrest and mesenchyma and neuroectoderm).